Efficiencies Evaluation of Photocatalytic Paints Under Indoor and Outdoor Air Conditions - Salvadores, Federico; Reli, Martin; Alfano, Orlando M.; Kočí, Kamila; Ballari, María de los Milagros (Frontiers in Chemistry, 2020)
The removal of indoor and outdoor air pollutants is crucial to prevent environmental and health issues. Photocatalytic building materials are an energy-sustainable technology that can completely oxidize pollutants, improving in situ the air quality of contaminated sites. In this work, different photoactive TiO2 catalysts (anatase or modified anatase) and amounts were used to formulate photocatalytic paints in replacement of the normally used TiO2 (rutile) pigment. These paints were tested in two different experimental systems simulating indoor and outdoor environments. In one, indoor illumination conditions were used in the photoreactor for the oxidation of acetaldehyde achieving conversions between 37-55%. The other sets of experiments were performed under simulated outdoor radiation for the degradation of nitric oxide, resulting in conversions between 13-35%. This wide range of conversions made it difficult to directly compare the paints. Thus, absorption, photonic and quantum efficiencies were calculated to account for the paints photocatalytic performance. It was found that the formulations containing carbon doped TiO2 presented the best efficiencies. The paint with the maximum amount of this photocatalyst showed the highest absorption and photonic efficiencies. On the other hand, the paint with the lowest amount of carbon doped TiO2 presented the highest value of quantum efficiency, thus becoming the optimal formulation in terms of energy use.